VCO Production Using the Steeping Method to Replace Heating in Sindanglaya Village - Yulis Sutianingsih (SATRIA BHAKTI, 2026)
One of the implementations of the Tri Dharma of Higher Education is the KKM (Student Work Lecture) activity whose main activity is to carry out community service. The KKM activity for the 2024-2025 academic year, especially group 19, was carried out in Sindanglaya Village, Cinangka District, Serang Regency. In this year's KKM activity, students have a special program, one of which is the manufacture of VCO (Virgin Coconut Oil) using the incubation method. This method was chosen because it is very easy to do, without additional materials, without using heat energy so that it is expected that the main content will still maintain its quality. The manufacture of VCO was chosen because of the geographical location of Sindanglaya Village which is on the coast so it is very easy to get the raw material for making VCO, namely coconut. The VCO manufacturing activity was carried out on August 7, 2025 by socializing the manufacturing method, then conducting direct practice of making VCO which was attended by 20 participants from Teachers, Parents, Students of RA Al-Khairiyah branch and residents around Sindanglaya Village. This activity can provide education on how to obtain higher quality VCO and can also provide business opportunities for the local community, so that they can increase processed coconut products that have higher economic value.